Persistent Salmonella enterica serovar Typhimurium Infection Increases the Susceptibility of Mice to Develop Intestinal Inflammation - Schultz, Bárbara M.; Salazar, Geraldyne A.; Paduro, Carolina A.; Pardo-Roa, Catalina; Pizarro, Daniela P.; Salazar-Echegarai, Francisco J.; Torres, Javiera; Riedel, Claudia A.; Kalergis, Alexis M.; Álvarez-Lobos, Manuel M.; Bueno, Susan M. (Frontiers in Immunology, 2018)
Chronic intestinal inflammations are triggered by genetic and environmental components. However, it remains unclear how specific changes in the microbiota, host immunity or pathogen exposure could promote the onset and exacerbation of these diseases. Here, we evaluated whether Salmonella enterica serovar Typhimurium (S. Typhimurium) infection increases the susceptibility to develop intestinal inflammation in mice. Two mouse models were used to evaluate the impact of S. Typhimurium infection: the chemical induction of colitis by Dextran Sulfate Sodium (DSS) and IL-10-/- mice, which develop spontaneous intestinal inflammation. We observed that S. Typhimurium infection makes DSS-treated and IL-10-/- mice more susceptible to develop intestinal inflammation. Importantly, this increased susceptibility is associated to the ability of S. Typhimurium to persist in liver and spleen of infected mice, which depends on the virulence proteins secreted by Salmonella Pathogenicity Island 2-encoded Type Three Secretion System (TTSS-2). Although immunization with a live attenuated vaccine resulted in a moderate reduction of the IL-10-/- mice susceptibility to develop intestinal inflammation due to previous S. Typhimurium infection, it did not prevent bacterial persistence. Our results suggest that persistent S. Typhimurium infection may increase the susceptibility of mice to develop inflammation in the intestine, which could be associated with virulence proteins secreted by TTSS-2.